Linguistic identity and the stylistics of nativisation in Adichie’s Purple Hibiscus - Ononye, Chuka Fred (Penerbit Universiti Kebangsaan Malaysia, 2018)
Existing linguistic studies on prose discourse have largely focused on what Nigerian English forms (NEFs) are utilised to better express Nigerian writers’ themes, but have not accommodated how the NEFs have creatively been deployed to show the writers’ identity in the discourse. In filling this gap, therefore, the paper takes a text-linguistic approach, relying on insights from David Jowitt’s view on Popular Nigerian English (PNE), Michael Halliday’s systemic functional grammar, and aspects of stylistics discourse, in examining some of the structural features of NEFs in Chimamanda Adichie’s Purple Hibiscus (PH), with a view to establishing how the Igbo variety of the PNE has motivated the use of NEFs in the novel. Five preponderant structural patterns were identified through which nativisation occurs in the text: colloquial utterances, transliteration, Igbo-influenced structure of clause, code mixing, and code switching. These structural instances of NEFs in PH have been observed to be tilted towards the Igbo variety of the PNE as motivated by the native language of the author. Thus, the NEFs are constrained by the linguistic pattern and socio-cultural world-view of the Igbo, which give the speakers of English in the region a linguistic identity that includes them in the PNE at large.